PATTERNS OF GENDER RELATIONS ON WOMEN MIGRANT WORKERS FAMILY IN THE PEKALONGAN REGENCY - Fikri Aminullah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2015)
This Qualitative research of gender perspective, departing from the issue of the high divorce family female migrant workers, which is indicated by a shift in the pattern of gender relations in their family. The research location in Pekalongan. Determination of informants using purposive, developed with snowball. The collection of data through observation, interviews and document study. Analysis techniques using Interaktive Model. Checking the validity of the data using triangulation. The results showed that, shifting patterns of gender relations within the family women migrant workers occur because of, the economic base into the hands of his wife and cultural influences from abroad where women migrant workers work. The structure of the shift pattern of gender relations within the family women migrant workers are categorized in several models, namely: structural shift from vertical patriarchis to horizontal relationship; from the vertical patriarchis to vertical matriarkhis and; from horizontal relationship to vertical matriarkhis. The nature of the shift there are revolutionarily and evolutionary or dynamic equilibrium.